2011
DOI: 10.1371/journal.pone.0020591
|View full text |Cite
|
Sign up to set email alerts
|

From In Vivo to In Vitro: Dynamic Analysis of Plasmodium falciparum var Gene Expression Patterns of Patient Isolates during Adaptation to Culture

Abstract: Plasmodium falciparum erythrocyte membrane protein 1 (PfEMP1), encoded by the var gene family, plays a crucial role in disease virulence through its involvement in binding to various host cellular receptors during infection. Growing evidence suggests that differential expression of the various var subgroups may be involved in parasite virulence. To further explore this issue, we have collected isolates from symptomatic patients in south China-Myanmar border, and characterized their sequence diversity and trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 58 publications
0
24
0
1
Order By: Relevance
“…Previous studies reported that UpsA var genes from patient isolates were down-regulated faster than other var genes during adaptation to culture (Peters et al, 2007; Zhang et al, 2011). The HB3 repertoire contains seven UpsA genes, all but one of which are subtelomeric.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies reported that UpsA var genes from patient isolates were down-regulated faster than other var genes during adaptation to culture (Peters et al, 2007; Zhang et al, 2011). The HB3 repertoire contains seven UpsA genes, all but one of which are subtelomeric.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have noted that var genes located near the centres of chromosomes tend to be more highly transcribed in vitro than those in subtelomeric location (Frank et al, 2007; Peters et al, 2007; Enderes et al, 2011; Zhang et al, 2011; Fastman et al, 2012), and it has been suggested that this might be due to low deactivation rates (Frank et al, 2007). In this study, we found that high transcription levels are confined to a subset of central genes that encode only four PfEMP1 binding domains (termed Type 1 var genes [Gardner et al, 2002]) and, importantly, are the result of high activation biases rather than low off-rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recently published var expression studies from malaria patients, however, support the idea that host factors contribute to var gene transcriptional control. Unlike in vitro cultured parasites, ups A-type var genes were frequently expressed in P. falciparum-infected patients (Bachmann et al, 2011;Zhang et al, 2011b). Subsequent cultivation resulted in random expression of many var genes mostly of the ups B and C-type.…”
Section: Switching and External Factorsmentioning
confidence: 99%
“…Porém, não está claro se a capacidade de aderir a mais de um receptor se deve à expressão de um gene var que codifica uma PfEMP1 "poliaderente" ou se é devido à co-expressão de genes var (Joergensen et al, 2010). (Frankland et al, 2007 Adicionalmente, a literatura também relata alterações no padrão de adesão de isolados de campo (Gray et al, 2003;Zhang et al, 2011). Experimentos em fluxo com isolados, provenientes de pacientes que foram a óbito devido à malária cerebral, que aderiam bem a ICAM-1 estaticamente, não se mostraram eficientes em aderir a ICAM-1 em fluxo, e o inverso também foi observado, o isolado que se ligava menos a ICAM-1 estaticamente, obteve uma adesão em fluxo mais eficiente (Gray et al 2003).…”
Section: Genotipagem Da Hemoglobinaunclassified